Management of patients with posterior urethral valves “from the fetus to adolescence”: French national diagnostic and care protocol (NDCP) - Alaa El-Ghoneimi; Luke Harper; Ugo Maria Pierucci; Thomas Blanc; Jonathan Rosenblatt; Nicolas Sananes; Sophie Dreux; Marianne Alison; Fred Avni; Stéphane Decremer; Veronique Baudouin; Sayaka Oguchi; et al. (Orphanet Journal of Rare Diseases)
Abstract Posterior urethral valves (PUV) are congenital anomalies characterized by the persistence of mucosal folds in the urethra, leading to various degrees of obstruction. They are the most common cause of lower urinary tract obstruction in fetuses and children, with a severe prognosis, as one-third of affected children develop end-stage renal disease before adulthood. The French National Diagnostic and Care Protocol (NDCP) aim to provide healthcare professionals with guidelines for the optimal diagnostic and therapeutic management of PUV from the fetal stage to adolescence. The guidelines emphasize early diagnosis through prenatal ultrasound and the importance of a multidisciplinary approach involving pediatric urologists, nephrologists, and other specialists. It outlines prenatal interventions such as vesico-amniotic shunting and postnatal surgical options like endoscopic valve ablation to alleviate obstruction and preserve renal function. Long-term follow-up is crucial for monitoring renal function, managing bladder dysfunction, and preventing complications such as urinary tract infections and chronic kidney disease. The guidelines also identify off-label pharmaceuticals and necessary specialty products not typically covered by insurance. By standardizing care pathways and promoting consistent, high-quality care, the guidelines aim to improve the prognosis and quality of life for children with PUV, setting a benchmark for managing this rare condition in pediatric urology.